Reforma rolna – współczesne zagadnienia stosowania prawa - Kiczka, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The decree of the Polish Committee of National Liberation of September 6, 1944 on the implementation of agrarian reform was one of the normative acts fundamentally shaping the previous system of “people’s democracy”, but also, in its multiple effects, is also important for the contemporary social relations of a democratic state of law. Pursuant to paragraph 5 of the regulation on the execution of the decree on the implementation of agrarian reform, the competence of public administration bodies to decide, by way of an administrative decision, whether a given property falls under the provisions of article 2 section 1 letter e of the agrarian reform decree was established only in relation to a specific group of land properties. In this area, the executive power bodies are entrusted with public law competence to decide on the legal situation of an individual in this respect. Basically, the application of public law, including regulations regarding agrarian reform, was not subject to judicial control to the necessary extent during the period of the Polish People’s Republic. For obvious reasons, the protection of the rights of owners whose real estate was taken over for the purposes of agrarian reform was marginalized or even excluded. Only the restitution of the administrative judiciary opened up new possibilities in this field. Nowadays, the jurisprudence of the Constitutional Tribunal emphasizes that the reliability and efficiency of operation of public institu- tions, in particular those institutions that were created to implement and protect the rights guaranteed by the Constitution, are values that have a constitutional rank. The importance of the principle of reliability and efficiency of operation — in relation to the courts — according to the Constitutional Tribunal is expressed in particular in the fact that the justice system (courts) is to implement, broadly speaking, the two most important constitutional guidelines, namely to ensure the reliability and efficiency of the courts as public institutions. Therefore, the position of the Supreme Administrative Court should ultimately be considered fully accurate, that in matters of agricultural reform submitted to public administration bodies for adjudication pursuant to paragraph 5, section 1 of the regulation, currently — in the conditions of a democratic state of law — there is a possibility of two-instance adjudication in administrative proceedings, as well as judicial review of these decisions through two-instance administrative court proceedings, which fully meets the constitutional requirements and current European standards.
Keywords: reforma rolna; stosowanie prawa; sądy administracyjne